Analysis of Total Anthocyanin Levels in Hibiscus (Hibiscus rosa-sinensis L.) Preparations by Differential pH Method Using UV-Vis Spectrophotometry - Suryani*, Elsa; Muna, Laili Nailul (Universitas Syiah Kuala, 2024)
Red hibiscus is a plant that contains anthocyanins and flavonoids which act as natural dyes and preservatives. Anthocyanins are attractive coloring substances and are not harmful to health, therefore they are widely used in the food and pharmaceutical industries. The maximum allowable daily intake of anthocyanins is 0.25 mg/kg body weight. Excessive intake of anthocyanins can cause poisoning. This study aims to determine the total anthocyanin content in hibiscus extract. The method used to analyze anthocyanin levels is the differential pH method using UV-Vis spectrophotometry. The main advantage of this method is that it provides a simple way to measure very small amounts of substances. The results of the research explained that the qualitative analysis showed that the sample was positive for containing anthocyanins because the acid reagent HCl remained red, this was due to the formation of flavilium. The sample with the base reagent (NaOH) changes color to green due to the formation of a carbinol pseudobase structure. Quantitative analysis of anthocyanins showed that in 10.8876 grams of extract there was an anthocyanin content of 72.4731 mg/L at a dilution of 10 ml. The high level of total anthocyanin in the thick hibiscus extract preparation can be influenced by several things such as the temperature during the drying process, the length of maceration time, the concentration of the solvent used, and the high intensity of light